Integrative psychotherapy in action - Erskine, Richard G. (Karnac Books Ltd., 2011)
What is integrative psychotherapy? How effective is the integrative approach to therapy? And what are its limitations? Answering these and other significant questions, this insightful volume provides the working clinician with a practical guide to using an integrative approach to psychotherapy. Erskine and Moursund, both experienced psychotherapists, begin their discussion with a masterful theoretical overview which integrates diverse concepts from various therapy techniques such as psychoanalysis, client-centred therapy, and Gestalt therapy. The authors then use transcripts of actual therapeutic sessions (with explanatory comments interjected) to provide the reader with a broader understanding of both theory and its application in therapy - and to capture some of the elusive essence of the ongoing therapy interview. Unique in its attention to detail, as well as to the therapist's own decision-making process, advanced students and therapists alike will find this volume an invaluable resource.